The psychological assessment of children's learning and behavioural problems as manifested in Kwazulu primary schools - Sibaya, Patrick Themba (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Ed.) -- University of Stellenbosch, 1992.